Identification of different user types for designing household food waste interventions. Issue 4 (4th July 2021) - Coskun, Aykut
ABSTRACT: To date, designers have developed various interventions to support users in reducing their household food waste. When designing food waste interventions, it is essential to have a clear understanding of target users' characteristics and consider the diversity in these characteristics. Although there are studies exploring user diversity in the context of sustainable behaviours, the literature lacks studies investigating food waste as a case. This paper explores user diversity in household food waste behaviour and identifies four user types that need to be considered when designing food waste interventions: Conservers, Considerates, Reluctants, and Prodigals . It further gives suggestions on how designers can select target user types and interventions according to their characteristics. It concludes that a design team should target all of the user types in a target population as much as possible and use a combination of different interventions types to create an impactful solution.